Perlindungan Hukum Terhadap Ketentuan Me-Review Produk di Media Sosial (International Forum of Researchers and Lecturers, 2024)
The era of the digital economy in Indonesia has made buying and selling transactions easier and faster to carry out. By using social media, consumers can channel their opinions, criticism and suggestions regarding the products/services they consume to business actors in various forms. One of them is in the form of a review (overview) of products/services expressed through photos or videos. However, this activity has reaped pros and cons in society, because it is considered that this activity actually tarnishes a good name. This research aims to examine the form of legal protection for the provisions for reviewing products on social media. The sources of legal materials used in this writing are firstly primary legal material sources which have binding force, secondly secondary legal material sources which are legal materials originating from the results of a literature review by reading books, legal journals, and articles that are in accordance with the law. the issue being faced. Data were analyzed using qualitative methods. This research uses a normative research type using a deductive thinking approach. The data that has been analyzed shows that legal protection for the provisions for reviewing products on social media is stated in Law Number 12 of 2005 article 23 paragraph (2) concerning Human Rights, Article 44 paragraph (3) UUPK, and criminal sanctions for perpetrators are stipulated in the UUPK which can be sentenced to prison and a fine.